Photoshop CS3 photo effects cookbook - Shelbourne, Tim, 1965- (O'Reilly digital studio., 2007)
Whether you're just getting getting into Photoshop or have been using it for a while, you know that it's a many-faceted application that can be somewhat overwhelming to master. With 53 easy-to-follow recipes, Photoshop CS3 Photo Effects Cookbook shows you how to use Photoshop CS3 to simulate classic camera and darkroom techniques and special effects--without making you first learn Photoshop inside and out. Using the improved Vanishing Point, Lens Blur, and Black & White filters Creating graphic art effects: posterization, watercolor, pen and ink Working with lighting effects: neon glows, lens flares, fire and flame effects Simulating natural phenomena: rain, snow, and lightning Adapting traditional techniques: film grain, contrast masks, hand-tinting, cross-processing Adding motion blurs and other special effects Assembling multi-layered images and photomontages Packed with hundreds of full-color images, step-by-step instructions, and many practical tips, this book-and Adobe Photoshop CS3- are all you need to create professional graphic art effects from almost any image source. The book covers